Economic Geography : the Integration of Regions and Nations. - Combes, Pierre-Philippe (Princeton University Press, 2011)
Economic Geography is the most complete, up-to-date textbook available on the important new field of spatial economics. This book fills a gap by providing advanced undergraduate and graduate students with the latest research and methodologies in an accessible and comprehensive way. It is an indispensable reference for researchers in economic geography, regional and urban economics, international trade, and applied econometrics, and can serve as a resource for economists in government. Economic Geography presents advances in economic theory that explain why, despite the increasing mobility of c.